Hazard reporting: How can it improve safety?. (October 2021) - Havinga, Jop; Bancroft, Kym; Rae, Andrew
Highlights: Hazard reports are used towards different goals than incident reports. The concept of hazards poorly fits with what people expects facilitates learning. Efforts to increase the number of safety reports can have counterproductive effects. Operators view hazard reporting as a way to reach out to other groups. Abstract: The academic literature presents hazard reporting as an extension of incident reporting. Hazards are presented as more safety data to collect, data that allows for proactive actions, but feeds into a similar learning process. In this paper, we use ethnographic data to examine whether either view holds up both critically and empirically. Based on both literature and data, five possible functions for hazard reporting systems were identified; sharing experiences, organisational learning, extending organisational memory, performance monitoring, and coordinating remedial actions. The data was then explored to test whether the hazard reporting system was facilitating these functions in practice. It was found that in practice, hazard reporting mostly fulfilled the role of coordinating remedial action, and pertained less to any of the learning and memory-related functions. Hazard reporting was found to be unsuitable for performance monitoring. From these findings follow general takeaways - that hazard reporting is, in practice, different from incident reporting; the word hazard is a poor choice to structure learning effort around; trying to increase reporting can be counterproductive for learning efforts, and reporting is valued for its ability to reach out to others within an organisation.